Fabrication of Hemispherical and Gradient-Index ZnO Nanostructures and Their Integration into Microsystems. Issue 10 (18th July 2015) - Pavlovski, Joey; Myrskog, Stefan; Dufour, Pascal; Gabardo, Christine M.; Soleymani, Leyla
Abstract : Zinc oxide (ZnO) is a wide and direct bandgap semiconductor, which can be structurally tuned to create materials having an extensive range of simple and complex morphologies. The ability to translate this structural tunability to functional tunability has made ZnO the subject of intense scientific and engineering research. ZnO films composed of nanoscale hemispherical and gradient-index building blocks have great potential for use in photovoltaic devices as antireflection, light trapping, and light scattering elements. Electrodeposition is an inexpensive, scalable, and low-temperature method for depositing nanostructured materials directly on device surfaces. In this work, we investigate the electrodeposition parameter space for developing hemispherical and gradient-index nanostructures directly on semiconducting substrates. We observe that lowering the nucleation and growth rate of ZnO in a hydrogen peroxide bath transforms the structures from continuous films to the desired hemispherical and gradient index morphologies. Furthermore, we combine this bottom-up fabrication method with top-down photolithography for integrating these structures into periodic microelectrode configurations. We optically characterize these nanostructured films and observe that the nanostructured ZnO film reduces reflection significantly from silicon surfaces in the 0.35 μm (from 49% to 3.6%) to 1.3 μm (from 35% to 21%) wavelength range.